2002
DOI: 10.1039/b201246d
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular organization of block oligomers based on rod-shaped mesogen into liquid crystalline assembly

Abstract: Synthesis, structures, properties and applications of materials particularly those associated with advanced technologyRod-coil molecules containing rigid rods and flexible coils are self-assembled into various liquid crystalline assemblies, that is, smectic, hexagonal columnar, bicontinuous cubic, honeycomb like, discrete micellar phases and so on. Cover picture shows selfassembly of rod-coil molecules into organized bundles (3-D body centered tetragonal structure) (upper) and organized honeycombs (3-D hexagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 36 publications
1
45
1
1
Order By: Relevance
“…Under similar conditions, the coupling reactions of 4-methoxybromobenzene also underwent with 88% yield (entries 5). However, the coupling reactions of 4-methylbromobenzenes underwent only in 10% yield (entries 6) and no reaction took place in bromobenzenes including electron-deficient substrates (entries 7,8), it showed that the more electrons on the benzene ring the more liable coupling reactions will happen. The crosscoupling reaction of aryl chloride including electron-rich and electron-deficient substrates didn't take place because which is generally unreactive under the conditions employed to couple aryl bromides and aryl iodides (entries 9-11).…”
Section: Self-organization Of Amphiphilic Diblock Rod-coil Moleculementioning
confidence: 94%
See 1 more Smart Citation
“…Under similar conditions, the coupling reactions of 4-methoxybromobenzene also underwent with 88% yield (entries 5). However, the coupling reactions of 4-methylbromobenzenes underwent only in 10% yield (entries 6) and no reaction took place in bromobenzenes including electron-deficient substrates (entries 7,8), it showed that the more electrons on the benzene ring the more liable coupling reactions will happen. The crosscoupling reaction of aryl chloride including electron-rich and electron-deficient substrates didn't take place because which is generally unreactive under the conditions employed to couple aryl bromides and aryl iodides (entries 9-11).…”
Section: Self-organization Of Amphiphilic Diblock Rod-coil Moleculementioning
confidence: 94%
“…[1][2][3][4][5][6] An example of a self-assembling system is provided by rod-coil molecules, which have a strong tendency to self-organize into a variety of supramolecular structures in nano-scale dimensions. [7][8][9][10][11][12] Amphiphilic rod-coil molecules are of great interest for nano-functional materials due to its intrinsic self organization property at the aqueous solution and used as suitable biomembrane and supra-nanoreactor system. [13][14][15][16][17][18][19] Lee and Jin have previously synthesized an amphiphilic coil-rod-coil molecule that contains polymerizable vinyl groups in the middle of the rod segment, which self-organizes into 2-D columnar structure and transfers to cross-linking nano-fiber via photopolymerization at the liquid crystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 presents a symbolic picture of the carbosilane dendrimer (1) in which the cations are complexed by the oxygens of the TEG-arms, which is a well-known behavior of polyethylene glycols towards metal cations. [18][19][20] To obtain a predication about the selectivity of compound 1, the concerning cations were added, as described in the Experimental part, before starting the mass spectrometrical investigations. From the resulting mass spectra, only the base peaks, the [M+2A] 2+ signals (A = alkali metal cations), were interpreted.…”
Section: Resultsmentioning
confidence: 99%
“…In these polymolecular assemblies with low molecular weight which are the basis for "bottom up engineering", the hydrophilic parts and the lipophilic parts of the amphiphiles are segregated into nano-scale compartments (typically between 1 and 100 nm), whereby changing the degree of curvature of the interfaces between the incompatible nano-phases generates sequences with different mesophase morphologies [6,7]. In recent years, supramolecular organization constructed by adding block low molecular weight molecules [8], block oligomers [9], or block copolymers [10] to rodshaped mesogen liquid crystalline assemblies have been reported, respectively. Here, I would like to discuss the functional structural concept of block molecular design for self-assembly of molecules.…”
Section: And 2)mentioning
confidence: 99%